Pengaruh Berbagai Jenis Pupuk Kandang Dan Frekuensi Penyiangan Terhadap Pertumbuhan Dan Hasil Tanaman Selada Keriting (Lactuca sativaL.) - Oryza Affandina Sani; Hanny Hidayati Nafi’ah; Novriza Satia (Universitas Garut, 2021)
Manure is a fertilizer that is widely used in organic agriculture. The purpose of this study was to determine whether there was a best combination of manure used and weeding frequency on plant growth and yields. The research was done in Cimaragas, CilawuDistrict, GarutRegency from August to September 2020. The research used an experimental method with factorial randomized block design (FRBD) consisted of 2treatment factors with 3replications, namely: First treatment (Types of Manure) consisted of goat manure (k1),cow manure (k2),chicken manure (k3),and NPK fertilizer (k0)as control. Second treatment (Weeding frequency) consisted of without weeding (p0),2times of weeding (p1),and4times of weeding (p2).The results showed that there was an interaction on the observation parameters of dry weight and leaf area of the plant. The combination that gives the best influence was cow manure with 2times of weeding.Keyword: lettuce, manure, weeding